Service Quality, Customer Satisfaction, and Repurchase Intention in Atalilah Catering at Belopa City - Ansri Jayanti; Sultan; Yusriani Yusuf; Nina Fapari Arif; Tasrim; Eka Muzalfitri Ridwan (SAJMR : Southeast Asian Journal of Management and Research, 2023)
Intention is the first step before making a decision to use a product. This position is primarily determined by the strategy of the company marketing the product. So, encouraging customer buying interest is strategic in "binding" customers. The research aims to analyze the relationship between service quality and customer satisfaction on purchasing interest. This research was conducted at the Atalilah Catering business, Luwu Regency, South Sulawesi-Indonesia. The research population is customers. The research sample was 50 respondents. The sampling technique uses accidental random sampling. The research used previous regression analysis, first testing the research instrument. The research results show that service quality does not show a significant influence on repurchase intention. This does not mean that service is not needed to encourage repurchase interest. However, the current service conditions are standard services. Food businesses are also inseparable from community activities such as family and office activities. Meanwhile, customer satisfaction shows significant results. This condition indicates that customer satisfaction is important in the catering industry. This customer satisfaction reflects variables that play a role in increasing customers' intentions to use services. Therefore, it is indispensable to pay attention to the position of customer satisfaction.